Barriers for Tdap Vaccination in Pregnancy [38C]. (May 2017) - Ashby, Mary; Roussos-Ross, Dikea; Julie DeCesare, Hanna Peterson; Vidrine, Samantha; Floy, Elizabeth
Abstract : INTRODUCTION: The American College of Obstetricians and Gynecologists (the College) and the Centers for Disease Control and Prevention recommend the Tdap vaccination in the 3rd trimester of pregnancy in order to protect newborns from neonatal pertussis. The purpose of this study was to identify barriers to Tdap vaccination in pregnancy. METHODS: A multisite study was conducted at UF Health and Sacred Heart Hospitals in Florida. This study was performed in conjunction with the College's District XII Committee for Healthcare of Underserved Women. Admitted postpartum patients were offered a survey to complete on day of discharge. RESULTS: A total of 162 patients completed the survey. Forty-eight patients had private or government-sponsored insurance (TriCare, Medicare, VA) and 114 patients had Medicaid. Of private/gov-insured patients, 62.5% (30) received Tdap in the 3rd trimester compared to 21.9% (25) of patients with Medicaid. Of those who did not receive Tdap in the third trimester, 50% (6) of private/gov-insured patients cited education while 34% (21) of patients with Medicaid cited lack of access. Of patients who did not receive Tdap in the third trimester, 46.5% (53) of the Medicaid patients received it postpartum compared to 37.5% (18) of private/gov-insured patients. CONCLUSION: Patients with Medicaid insurance are less likely to receive the Tdap vaccine in the 3rd trimester than those with private or other government-sponsored insurances. In patients who did not receive Tdap, those with Medicaid cited lack of access as the primary reason they did not receive the vaccine while those with private/gov-insurance cited education-related reasons. Tdap vaccination rates in pregnancy could be increased by improving both education and access to patients.